Cancer and the LGBT Community: Unique Perspectives from Risk to Survivorship - Boehmer, Ulrike (Springer, 2015)
This book covers the scope of current knowledge of cancer in the LGBT community across the entire cancer continuum, from understanding risk and prevention strategies in LGBT groups, across issues of diagnosis and treatment of LGBT patients, to unique aspects of survivorship and death and dying in these communities. Each chapter includes an in depth analysis of the state of the science, discusses the many remaining challenges and unanswered questions and makes recommendations for research, policy and programmatic strategies required to address these. Focus is also placed on the diversity of the LGBT communities.